2018
DOI: 10.7554/elife.33183
|View full text |Cite
|
Sign up to set email alerts
|

Polycystin-2 is an essential ion channel subunit in the primary cilium of the renal collecting duct epithelium

Abstract: Mutations in the polycystin genes, PKD1 or PKD2, results in Autosomal Dominant Polycystic Kidney Disease (ADPKD). Although a genetic basis of ADPKD is established, we lack a clear understanding of polycystin proteins’ functions as ion channels. This question remains unsolved largely because polycystins localize to the primary cilium – a tiny, antenna-like organelle. Using a new ADPKD mouse model, we observe primary cilia that are abnormally long in cells associated with cysts after conditional ablation of Pkd1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
185
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(197 citation statements)
references
References 86 publications
12
185
0
Order By: Relevance
“…Thirdly, our results show that the PC1/PC2_AA channel has a larger or more flexible pore, and higher permeability to most monovalent cations tested in this study (i.e., Na + , Li + , Cs + , DMA + , DEA + , and TEA + ) when compared to PC2_AA alone (Fig 5). The fact that the homomeric PC2 channel has low Ca 2+ permeability [11,22] while the PC1/PC2 channel complex has much higher Ca 2+ permeability indicates their very distinct physiological roles and thus contributions to ADPKD. Collectively, these results tell us that the heteromeric PC1/PC2 channel and the homomeric PC2 channel are two distinct channels that likely have their unique functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, our results show that the PC1/PC2_AA channel has a larger or more flexible pore, and higher permeability to most monovalent cations tested in this study (i.e., Na + , Li + , Cs + , DMA + , DEA + , and TEA + ) when compared to PC2_AA alone (Fig 5). The fact that the homomeric PC2 channel has low Ca 2+ permeability [11,22] while the PC1/PC2 channel complex has much higher Ca 2+ permeability indicates their very distinct physiological roles and thus contributions to ADPKD. Collectively, these results tell us that the heteromeric PC1/PC2 channel and the homomeric PC2 channel are two distinct channels that likely have their unique functions.…”
Section: Discussionmentioning
confidence: 99%
“…How these mutations lead to ADPKD is unclear, and the molecular mechanism of the function of the PC1/PC2 complex is largely unknown. The Ca 2+ conductance by PC2 or PC1/PC2 complex is also hotly debated [7,[9][10][11][12][13][14][15][16]. However, thus far the in vivo stimuli of this complex remain unknown, although previous studies suggested fluid flow as the potential stimulus [8] and Wnt proteins as candidate ligands [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…renal cortical collecting duct cells [139,140], where they were initially proposed to form a receptor-channel complex [141] that functions as a mechanosensitive Ca 2+ channel activated by fluid flow [142]. This hypothesis has been challenged by others [143,144], and recent work from David Clapham's lab using primary cultures of collecting duct cells isolated from kidneys of a new ADPKD mouse model, indicated that PC2, but not PC1, constitutes an essential ion channel subunit in the primary cilium that preferentially conducts K + and Na + and is potentiated by intraciliary Ca 2+ [145]. This study also showed that ciliary trafficking of PC2 occurs independently of PC1, contradicting several earlier reports [16,145], but in agreement with the recently solved homotetrameric structure of PC2 [146,147].…”
Section: Polycystin Signallingmentioning
confidence: 99%
“…Mutations in the pkd1 and pdk2 genes are associated with ADPKD. These genes encode the polycystins, PC1 & 2, the latter, referred to as TRPP2 (transient receptor potential polycystic), functions as a non-selective cation channel[3] [4]. Malfunction of either PC1 or PC2 leads to cyst formation [5]…”
Section: Introductionmentioning
confidence: 99%